Encapsulation of diflubenzuron in PEG-400 nanoparticles and evaluation pesticide activity against Helicoverpa armigera (Lepidoptera: Noctuidae) - Moosa Saber; Zeinab Ahmadi; Gholam Reza Mahdavinia; Reza Farshbaf Pourabad; Asmar Soleymanzadeh (Scientific Reports)
Abstract New formulation of diflubenzuron, was carried out through a simple and green route using polyethylene glycol (PEG). The insecticidal efficacy of PEG nano-capsules loaded with diflubenzuron (DFB) pesticide was evaluated against Helicoverpa armigera (Heb). The loaded nanoparticles had the spherical-shape and an average size of 80 ± 20 nm. In the acute toxicity bioassay, 2nd instar larvae of H. armigera were exposed to either DFB or fabricated DFB@NPs for 96 h. According to the results, the LC50 values were 316.87 and 139.36 µg a.i./mL for DFB and fabricated DFB@NPs, respectively. Also, the results of the contact toxicity bioassay against the egg stage of the pest revealed the LC50 values of 70.74 and 8.58 µg a.i./mL for DFB and nanoparticles prepared by PEG-400, respectively. Controlled release experiments showed that DFB@NPs releases the active ingredient over a prolonged period. This study revealed that the nanoformulation of diflubenzuron by PEG-400 can improve its insecticidal efficacy against H. armigera. The residue of DFB was analyzed via an HPLC and showed that after 3 weeks the residue of DFB and DFB@NPs were much lower than MRLs. Overall, our results indicated that the nanoformulation of diflubenzuron is more economical and environmentally friendly than traditional formulations.